PENGEMBANAGAN KAPABILITAS PEMBELAJARAN PADA ORGANISASI PETANI HORTIKULTURA DALAM PERSAINGAN PASAR - Pramono, Joko (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2010)
The farmers are mostly small-scale business organization capability, which face low, consequently their position in the market continues to displaced, their comparative advantage no longer produce much benefit. This problem has lasted a long time, so that raises the question of how their learning capabilities. The results of this study indicate that horticulture farmers to improve these capabilities must be developed by developing agricultural organizations are active, because farmers are generally passive in the organization